PENGARUH MODEL SNOWBALL THROWING TERHADAP HASIL BELAJAR IPS DI SD - Junisa, Atikah; Marli, Suhardi; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the effect of using snowball throwing model on the learning outcomes of Social Sciences fourth-grade students in SDN 68 Pontianak Barat. The research method used is an experiment with a quasi-experimental design with nonequivalent control group design. 63 students has been the sample of this research. Data collection techniques use measurement techniques. Instruments used are observation sheets and test result learning. Based on the calculation obtained by mean of learning result of post-test of control class 61,9 and average result of experiment class study of experiment class 80,16 so obtained tcount of post-test data equal to 7,40582 with ttable for signification level Î± = 5 % and dk = 61 for 1.99967, because tcount (7,40582)> ttable (1.99967) then Ha is accepted. Thus, there is a significant influence of using snowball throwing model on the learning outcomes of Social Sciences of the fourth-grade students of Sekolah Dasar Negeri 68 Pontianak Barat. From the calculated effect size (ES) is obtained at 1.33 (high criteria). It means the using snowball throwing model gives a high influence on the social science learning outcomes of fourth-grade students of SDN 68 Pontianak Barat.Â Key words : influences, snowball throwing, learning outcomes, social science.